Significant decrease in the prevalence of hepatitis C infection after the introduction of direct acting antivirals. Issue 9 (4th February 2020) - Rodríguez‐Tajes, Sergio; Domínguez, Ángela; Carrión, Jose Antonio; Buti, María; Quer, Joan Carles; Morillas, Rosa M; López, Carme; Torras, Xavier; Baliellas, Carme; Vergara, Merche; Forner, Montse; Zaragoza, Natividad; et al.
Abstract: Background and Aim: Accurate information on the epidemiology of hepatitis C and B infection is mandatory to establish a national/regional plan. We aim to update the prevalence of hepatitis C and B infection in Catalonia using point‐of‐care tests to analyze the risk factors related and to implement a linkage‐to‐care circuit. Methods: This is a community‐based study. A random list of adult individuals was retrieved from censuses of primary care centers. Point‐of‐care tests for anti‐hepatitis C virus (HCV) and HBV surface antigen (HBsAg) and a questionnaire for risk factor assessment were performed. Positive results were validated and a circuit for linkage‐to‐care was established. Results: A total of 3328 individuals were included. The anti‐HCV and HBsAg overall prevalence were lower than expected [1.02%, 95% confidence interval (CI) 0.65–1.39; and 0.52%, 95% CI 0.26–0.77, respectively]. Anti‐HCV positive subjects were mostly (88%) autochthonous. The prevalence increased with age; only 12% were under age 40. The associated risk factors were drug use, blood transfusion, relative with HCV, and diabetes. Notably, the prevalence of active infection was only 0.49% (95% CI 0.23–0.74), 40% less than previously reported, reflecting the impact of direct acting antiviral therapy. Differently, HBsAg positive subjects were mostly foreign migrants (53%) with no other risk factors. Despite the implementation of a linkage‐to‐care circuit, one third of HBsAg positive subjects were lost. Conclusions: The prevalence of HCV infection was lower than previously reported, showing a strong impact of direct acting antiviral therapy in the last years. Because of hepatitis B universal vaccination, HBV infection in Catalonia is mainly associated with migrant population. Linkage‐to‐care in patients with hepatitis B was challenging and warrants additional efforts.